(untitled) (Research, Society and Development, 2022)
The study aimed to analyze the dispensing of drugs derived from C. sativa L. in an Association in the city of João Pessoa-PB. This is a descriptive, exploratory study with a quantitative approach, in which monthly reports related to the dispensing of products derived from C. sativa L. were collected through the internal SINCTEC data system. During the period evaluated, a total of 21,131 products derived from C. sativa L. were dispensed, in which oils had the highest prevalence (90.7%), followed by ointments (5.3%), oils for vaporization (2 .4%) and sprays (1.6%), in which the oral route of administration gained prominence due to its greater predominance. Among the months analyzed, those with the highest output were November and December, totaling 7,469 products dispensed. In view of this, there was a growing demand for the availability on the market of several products obtained through the plant and the need for new studies involving dispensing, in which the pharmacist plays a prominent role, by guiding the patient about all pharmacological parameters. essential for adherence and effectiveness of treatment interacting directly in improving quality of life.